Tramadol non-medical use in Four European countries: A comparative analysis. (1st December 2020) - Iwanicki, Janetta L.; Schwarz, John; May, Kevin Patrick; Black, Joshua C.; Dart, Richard C.
Highlights: Four European national surveys have similar trends in prescription opioid misuse. Codeine is misused by the largest number of adults in all four countries. Tramadol misuse and injection are uncommon despite intravenous form availability. Abstract: Background: Understanding prescription medication misuse is challenging due to lack of consistent measures of misuse behaviors and prevalence between countries. Tramadol is an atypical opioid with a dual mechanism, and has low drug liking compared to conventional opioids. We evaluate tramadol misuse compared to conventional opioids utilizing a harmonized validated national survey across four countries: Germany, Italy, Spain, and the United Kingdom (UK). Methods: Data from the Survey of Non-Medical Use of Prescription Drugs (NMURx) Program online cross-sectional general population national surveys are analyzed from 2018 from four countries, with 45, 000 total responses. Misuse and abuse of tramadol, codeine, morphine, and oxycodone are compared, and national prevalence estimates calculated via calibration weighting. Rates are calculated per population and per drug availability. Supplemental data are included from patients entering treatment centres and poison centre exposures. Results: In 2018, distribution, misuse, and abuse of four prescription opioids show similar patterns across four countries. In all countries, codeine is misused by the largest number of adults (estimated 861, 181 in Italy to 4, 676, 680 in Spain in past 12 months). When adjusted for availability, tramadol is misused uncommonly with lowest or second lowest rates in all countries. Most abuse occurs by the oral route for all opioids, including tramadol with only 7.27 (Germany) to 54.92 (UK) cases per 100, 000 units sold. Conclusions: In four countries, tramadol misuse and abuse are infrequent both in absolute number of cases and in comparison to conventional opioids. Even with availability of intravenous tramadol formulations, misuse by injection is rare.